Studies on Occurrence of Trichinella spp. in Pork Meat Sold in Goa and Assam States of India - Kale, L. N.; Waghamare, R. N.; Vaidya, V. M.; Zende, R. J.; Paturkar, A. M.; Barua, A. G.; Shende, R. G. (International Journal of Livestock Research, 2018)
Trichinellosis is rare but an important zoonotic disease around the world which occurs due to consumption of raw or under cooked pork infected with parasitic larvae of the genus Trichinella. The occurrence of Trichinellosis in domestic animal populations is mainly due to poor management practices which allow them to feed on meat infected with Trichinella. Certain parts of the India such as Goa and Assam are reported to have high demand for pork and pork products which is met through good piggery farming system. However, no significant study has been carried out on occurrence of trichinellosis in these states. Considering the above facts, the present study was carried out to know the exact burden or existence of Trichinellosis in pigs of Goa and Assam states of India. A total of 421 samples (diaphragm and tongue/masseter muscle) were collected from different retail pork shops from Goa (n=346) and Assam (n=75). The samples so obtained were subjected to Acid-pepsin digestion assay for the detection of Trichinella larvae. None of the samples were found to be positive for Trichinella spp. indicating very low or zero occurrence in Goa and Assam. Further studies should direct towards continuous monitoring and surveillance of trichinellosis in pigs, to declare pig industry in these regions free from Trichinella.